GST Announcements: An Impact on Indian Stock Market Volatility - Jindal, Nisha; Aggarwal, Rachita (Gyan Management Journal, 2019)
GST is based on the principle on one nation, one market, one tax. The single biggest indirect tax regime is finally into force, dismantling all state hindrances with regard to trade. The single tax GST, has made India into a one unite market comprise of 1.3 billion citizens. It is seen that GST have its influence on the economy, so present paper studies whether the introduction have an impact on volatility of stock market of India. National Stock Exchange was used in the paper to represent the stock market of India. The daily closing prices was taken for the time period from April 2007 to 31st July 2017. The required data was taken from the website of the NSE (National Stock Exchange) which is www.nseindia.com. The software Eviews5 was used for analyzing the collected data. Different tools like OLS regression and Dummy Variable were used for the purpose.Nine sectors have been studied in total which are Automobile, Energy, PSU, Reality, Pharma, IT, FMCG, Finacial Services, and Banking. The results showed a mixed reaction as average returns decreased in some secors like automobile, pharma, financial services and banking while in all other sectors it increased.